Catchment landscape components alter relationships between discharge and stream water nutrient ratios in the Xitiao River Basin China - Changjun Gao (Nature Portfolio, 2021)
Abstract The terrestrial environment of a watershed is a source of potential carbon (C), nitrogen (N), and phosphorus (P) exports, and the hydrological regime provides the mechanism to turn the potential exports into reality when water is available. However, the extent to which the terrestrial environment alters the strength and nature of streamflow in transporting stream water nutrient ratios remains largely unknown. This study combined monthly stream discharge data with synchronously sampled stream water C:N:P ratios in 14 catchment streams in the Xitiao River Basin (XRB) in Zhejiang Province, China. The transport effect of streamflow on C:N:P ratios varied depending on the nutrient element, flow condition, and terrestrial environment. In the lower reaches of the XRB, there were negative relationships between C:N ratios, C:P ratios and watershed discharge, and positive relationships between N:P ratios and watershed discharge in both high and low flow conditions. In the middle and upper reaches of the XRB, the C:N-discharge relationship changed from negative to positive when the streamflow conditions altered from low to high flow. The C:P- and N:P-discharge relationships were negative regardless of high or low flows, but the regression coefficient significantly decreased with increasing streamflow. The C:N-discharge correlation over the course of the year shifted from negative to positive, as urban areas expanded within the catchment. The C:P-discharge relationship altered from negative to positive with more cropland and wetland but from positive to negative with a greater forest percentage and mean percentage slope. Our results indicate that changes in the terrestrial environment (e.g., the proportion of a particular land cover within a watershed) generally produced a threshold flow above which the coupling relationships between element fluxes from the terrestrial to riverine ecosystem changed sharply.